Kredit Usaha Rakyat (KUR) Regulation and Communication Factors towards Farmer Independence - Anna Gustina Zainal; Toni Wijaya; Selly Oktarina; Eko Wahyono; Pairulsyah Pairulsyah (Nyimak: Journal of Communication, 2021)
This study aims to determine: (1) the level of understanding of farmers about government regulations related to KUR funds in the Agriculture sector, (2) communication patterns and behavior as well as the use of farmer media types associated with KUR management in the agricultural sector (3) the relationship between communication patterns and behavior and the use of sector is aimed at educating farmers’ independence in managing their farming so that the food security program continuously improving. This research was designed as a descriptive correlational approach using the survey method. The research targets are farmer groups participating in the KUR program in the Agriculture sector covering five sub Districts, namely: Gading Rejo, Kotaa Agung, Gisting, Talang Padang, and Semaka, in Tanggamus District. Based on the results of the research, it is known that the understanding of farmers about the procedure for applying for KUR in the agricultural sector, rights and obligations and sanctions for violations, and management of KUR funds in the agricultural sector that they get on average are in the quite good category. Besides, there are significant differences in communication patterns and behavior as well as the use of types of media, causing farmers to understand different KUR programs in the Agriculture sector. Especially in the factor of communication patterns, communication behavior, and the use of the type of media that farmers choose. The relationship between communication patterns, individual farmer characteristics, behavior, communication, and the use of media types is quite varied.Keywords: Agriculture sector, communication patterns, farmer, regulation ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) tingkat pemahaman petani tentang peraturan pemerintah terkait dana KUR di sektor Pertanian, (2) pola dan perilaku komunikasi serta penggunaan jenis media petani yang terkait dengan pengelolaan KUR di bidang pertanian. sektor (3) keterkaitan antara pola komunikasi dan perilaku dengan pemanfaatan sektor bertujuan untuk mendidik kemandirian petani dalam mengelola usahataninya sehingga program ketahanan pangan terus meningkat. Penelitian ini dirancang dengan pendekatan deskriptif korelasional dengan menggunakan metode survei. Sasaran penelitian adalah kelompok tani peserta program KUR bidang Pertanian yang meliputi lima kecamatan, yaitu: Gading Rejo, Kota Agung, Gisting, Talang Padang, dan Semaka, di Kabupaten Tanggamus. Berdasarkan hasil penelitian diketahui bahwa pemahaman petani tentang tata cara pengajuan KUR di sektor pertanian, hak dan kewajiban serta sanksi atas pelanggaran, dan pengelolaan dana KUR di sektor pertanian yang mereka dapatkan rata-rata. termasuk dalam kategori cukup baik. Selain itu terdapat perbedaan pola komunikasi dan perilaku serta penggunaan jenis media yang sangat berbeda sehingga menyebabkan petani memahami berbagai program KUR di sektor Pertanian. Terutama pada faktor pola komunikasi, perilaku komunikasi, dan penggunaan jenis media yang dipilih petani. Hubungan antara pola komunikasi, karakteristik individu petani, perilaku, komunikasi, dan penggunaan jenis media cukup bervariasi.Kata Kunci: Sektor pertanian, pola komunikasi, petani, regulasi